Phytogeographic Meta-Analysis of the Vascular Epiphytes in the Neotropical Region - Marcusso, Gabriel Mendes [UNESP]; Kamimura, Vitor de Andrade [UNESP]; Borgiani, Renan [UNESP]; Menini Neto, Luiz; Lombardi, Julio Antonio [UNESP] (Springer Nature, 2022)
The Neotropical Region (NR) is one of the areas with the most plant diversity globally, and its richness of vascular epiphyte (VE) species is higher than Africa and Asia combined. This richness is a consequence of the heterogeneous climate and geological history of the region, both factors also being responsible for the plant distribution patterns. Here, we aimed to explore the phytogeographic relationships of the VE in the NR using 14,636 identified records from 173 surveys exclusively of VE, carried out in 14 countries and 23 biogeographic provinces, comprising 3849 identified species. We assessed the floristic patterns and relationships with climatic variables by multivariate analysis (cluster and ordination analyses). The clustering formed 13 main groups, partly corresponding to the biogeographic units of the NR. Our results demonstrate consistent floristic patterns confirmed through the analysis of floristic similarity, corroborating previous biogeographic classifications in well-studied areas, while broader patterns were found in poorly studied areas. We found a floristic gradient pattern, which allowed us to understand the relationships between environmental conditions and floristic patterns. Furthermore, we discuss our results under the light of the history that likely shaped the current distribution patterns and richness of the VE in the NR. The VE proved to be an important model for testing biogeographic classifications. We encourage the studies of this synusia in the several geographical gaps that remain in the NR, which undoubtedly will improve further studies and support conservationist policies.
Keywords: Amazon; Andes; Atlantic forest; Biogeography; Central America; Flora